2016
DOI: 10.4049/jimmunol.1600446
|View full text |Cite|
|
Sign up to set email alerts
|

IL-35 Decelerates the Inflammatory Process by Regulating Inflammatory Cytokine Secretion and M1/M2 Macrophage Ratio in Psoriasis

Abstract: IL-35 downregulates Th17 cell development and suppresses certain types of autoimmune inflammation such as collagen-induced arthritis and experimental autoimmune uveitis. Psoriasis is thought to be initiated by abnormal interactions between cutaneous keratinocytes and systemic immune cells. However, the role of IL-35 in psoriasis remains unclear. In this study, we assessed IL-35 in three well-known psoriasis models: a human keratinocyte cell line (HaCaT), a keratin 14 (K14)-vascular endothelial growth factor A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 51 publications
(62 reference statements)
8
63
0
Order By: Relevance
“…Similarly, Zhang et al . previously reported that the total amount of macrophages and the ratio of M1/M2 polarization were decreased by the IL‐35 in mice psoriasis models.…”
Section: Discussionmentioning
confidence: 85%
“…Similarly, Zhang et al . previously reported that the total amount of macrophages and the ratio of M1/M2 polarization were decreased by the IL‐35 in mice psoriasis models.…”
Section: Discussionmentioning
confidence: 85%
“…In contrast, in the keratin 14–VEGF–A‐transgenic mouse model, IL‐35 has different functions in regulating innate or adaptive immune reactions. For example, the IL‐10 concentrations or the number of CD4+CD10+ or CD4+CD25+Foxp3+ T cells can be dramatically induced by IL‐35; however, this cytokine can decrease the total number of macrophages and lower the ratio of M1/M2 macrophages, which are dominant in the innate immunity . However, Pablo et al .…”
Section: Discussionmentioning
confidence: 99%
“…As Zhang et al . have reported, in a typical psoriasis model, namely the keratin 14 K14–vascular endothelial growth factor A–transgenic mouse model, expression of IL‐10 and counts of CD4+CD10+ or CD4+CD25+Foxp3+ T cells in the peripheral blood increase markedly after treatment with IL‐35, indicating that IL‐35 plays a critical role in dysregulation of the immune system in pathogenesis of psoriasis .…”
mentioning
confidence: 99%
“…Recent results suggest that the plasma concentration of IL‐35 is lower in psoriasis patients than in healthy individuals . Furthermore, it was found that IL‐35 could alleviate the pathological characteristics of severe psoriatic lesions in K14‐VEGF‐A transgenic mice by reducing the ratio of the total number of macrophages to M1/M2 macrophages …”
Section: Il‐35 and Immune‐related Diseasesmentioning
confidence: 99%
“…47 lesions in K14-VEGF-A transgenic mice by reducing the ratio of the total number of macrophages to M1/M2 macrophages. 48,49…”
Section: Il-35 and Immune-related Diseasesmentioning
confidence: 99%